Perception of Justice and Employees’ Brand-Based Equity in the Service Sector: Evidence From Education Industry - Li, Lu (Frontiers in Psychology, 2022)
This study aims to investigate the impact of justice perception of the employees on three dimensions of employee brand-based equity under the mediating role of psychological contract fulfillment. For this purpose, data has been collected from the employees of education industry under the convenience sampling technique. In this regard survey method was used and questionnaires were distributed among 420 respondents, out of which 310 were received back and after discarding 32 partially filled questionnaire, useable responses were left 279. Data has been analyzed through structural equation modeling and PLS-SEM approached has been used in this regard through Smart PLS software. Measurement and structural models were assessed and all the indicators of reliability and validity has been found fit. Path estimation indicates that perception of justice promotes brand endorsement and brand allegiance while relationship of perception of justice and brand consistent behavior has not been found statistically significant. Moreover, it has also been found that perception of justice ensures employee that their psychological contract has met. Additionally, psychological contract fulfillment has found a mediating mechanism between the perception of justice and three dimensions of employee brand-based equity.